The Management of Social Phobia Ýn Residual-Type Schizophrenia with Cognitive Behavioral Therapy - Elif Þimþek Kaygusuz; Filiz Civil Arslan; Gizem Güneþ (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Having negative symptoms is the basic feature of residual-type schizophrenia and there is a direct proportion between the neurocognitive impairments associated with negative symptoms. Among the approaches used for the treatment of patients with schizophrenia, cognitive behaviour therapy is the one with the most evidence of efficacy. Cognitive behaviour therapy is considered to be beneficial for the residual symptoms after drug treatment. The social phobia leads among the anxiety disorders accompanying schizophrenia. According to the cognitive model, the impairment of social performance increases the severity of social phobia. The leading factor of this vicious circle is that the patients pay attention selectively to such cases in order to find evidence for their thoughts and beliefs that they are going to be evaluated negatively. In this paper, the cognitive behavioural therapy and formulation carried out with a patient, who has been followed for a long time with the diagnosis of residual-type schizophrenia and social phobia is reported. The purpose of the treatment is to interfere with the impaired functionality of the patient through cognitive and behavioural techniques by dealing with the medical treatment-resistant symptoms. To this end, firstly coping mechanisms are examined through the identification of avoidance and security providers, and then, the patient’s automatic thoughts and false beliefs are discussed depending on the cognitive perspective. The main part of the treatment has been completed by carrying out various investigations in order to increase the patients’ social performance via applying behavioural techniques. As a result, false beliefs are the indicators of the relationship between cognitive inability and negative symptoms and related to social functioning. By addressing these beliefs through cognitive behavioural therapy, the necessity of increasing the patient’s social activities and the relationship between social performance and social phobia are distinguished. [JCBPR 2015; 4(1.000): 38-46]